Review of current status, requirements and opportunities for building performance simulation of adaptive facades - Loonen, Roel C.G.M.; Favoino, Fabio; Hensen, Jan L.M.; Overend, Mauro (Journal of building performance simulation, 2017)
Adaptive building envelope systems have the potential of reducing greenhouse gas emissions and improving the energy flexibility of buildings, while maintaining high levels of indoor environmental quality. The development of such innovative materials and technologies, as well as their real-world implementation, can be enhanced with the use of building performance simulation (BPS). Performance prediction of adaptive facades can, however, be a challenging task and the information on this topic is scarce and fragmented. The main contribution of this review article is to bring together and analyse the existing information in this field. In the first part, the unique requirements for successful modelling and simulation of adaptive facades are discussed. In the second part, the capabilities of five widely used BPS tools are reviewed, in terms of their ability to model energy and occupant comfort performance of adaptive facades. Finally, it discusses various ongoing trends and research needs in this field.